Pendidikan Agama Islam Berbasis Pembelajaran Mendalam untuk Anak Usia Dini: Analisis Pembelajaran yang Penuh Perhatian, Bermakna, dan Menyenangkan di TK Alam Al-Hasan - Sri Wulan; Yulia Kuraesin Ila Rohima; Mirwan; Mohammad Rusli Hamdani; Mahmud; Pepen Supendi (At Turots: Jurnal Pendidikan Islam, 2026)
Islamic Religious Education (PAI) learning at the early childhood level plays a strategic role in building children’s spiritual, moral, and social foundations. However, PAI learning practices in early childhood education institutions remain predominantly verbalistic and memorization-oriented, thereby providing limited support for the meaningful and sustainable internalization of values. This study aims to analyze the implementation of deep learning based PAI through the approaches of mindful learning, meaningful learning, and joyful learning for early childhood learners at TK Alam Al-Hasan. This research employs a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation, and were analyzed thematically using source and method triangulation techniques. The findings indicate that mindful learning plays a role in fostering children’s early spiritual awareness through habituation of attention and simple reflection; meaningful learning enables children to internalize PAI values through real and contextual experiences; while joyful learning creates an emotionally safe and enjoyable learning environment that enhances children’s active engagement. From a theoretical perspective, the findings demonstrate that the pedagogical deep learning paradigm is aligned with Islamic educational theories, particularly the concepts of fiṭrah, tarbiyah, ta’dīb, and tazkiyah. This study contributes to the development of scholarly discourse on early childhood Islamic Religious Education and offers practical implications for teachers in designing contextual, humanistic, and character-oriented PAI learning for young children.